Nedd4-2 and the Regulation of Epithelial Sodium Transport - Rotin, Daniela; Staub, Olivier (Frontiers in Physiology, 2012)
Nedd4-2 is a ubiquitin ligase previously demonstrated to regulate endocytosis and lysosomal degradation of the epithelial Na+ channel (ENaC) and other ion channels and transporters. Recent studies using Nedd4-2 knockout mice specifically in kidney or lung epithelia has revealed a critical role for this E3 ubiquitin ligase in regulating salt and fluid transport in these tissues/organs and in maintaining homeostasis of body blood pressure. Interestingly, the primary targets for Nedd4-2 may differ in these two organs: while in the lung Nedd4-2 targets ENaC, and loss of Nedd4-2 leads to excessive ENaC function and to cystic fibrosis – like lung disease, in the kidney, Nedd4-2 targets the Na+/Cl- cotransporter (NCC) in addition to targeting ENaC. In accord, loss of Nedd4-2 in the distal nephron leads to increased NCC abundance and function. The aldosterone-responsive kinase, Sgk1, appears to be involved in the regulation of NCC by Nedd4-2 in the kidney, similar to its regulation of ENaC. Collectively, these new findings underscore the physiological importance of Nedd4-2 in regulating epithelial salt and fluid transport and balance.